Optimising referral pathways for patients with non-alcoholic fatty liver disease in the UK. Issue 3 (2nd March 2021) - Boyd, Alexander; Srivastava, Ankur; Rosenberg, William; Newsome, Philip N; Armstrong, Matthew J
Abstract : The increasing burden of non-alcoholic fatty liver disease means that robust clinical pathways need to be established in primary care to identify patients with advanced fibrosis who may benefit from specialist management. This article summarises the current landscape of non-invasive liver fibrosis tests and discusses the outcomes and lessons learned from non-alcoholic fatty liver disease pathways that have been instigated around the UK. The inherent challenges of implementing such pathways are explored, along with developing technologies, such as artificial intelligence blood testing, which will likely play an important role in helping to identify and risk-stratify more patients with non-alcoholic fatty liver disease in primary care in the future.